CSA Platform Annual Meeting - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Agriculture is the backbone of both Ethiopia’s livelihoods and the national economy, shaping the outcomes of all other sectors. Reliant largely on rainfall and subsistence farming, the country’s food systems are particularly vulnerable to a changing climate. “Climate change is a risk multiplier in terms of agricultural productivity, food and nutrition security,” said Dr. Dawit Solomon, East Africa Regional Program Leader for the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). To overcome these challenges, stakeholders have come together in Addis Ababa, Ethiopia to highlight entry points to harness the triple wins of climate-smart agriculture (CSA) in increased agricultural productivity, enhanced adaptive capacity and climate resilience, and reduced emissions where possible, for Ethiopia’s food systems and livelihoods.